ERGONOMIC POSTURAL ANALYSIS AT A DENTIST WORKSTATION (Fiep Bulletin - online, 2017)
Everyday activities cause damage to health, among those that give the greatest impact on the lives of workers aremusculoskeletal pains (lumbar) and psychological (stress). Therefore, this study is aimed at providing an ergonomic workanalysis (EWA) with professionals of the dental area in the city of Curitiba, State of Parana. Therefore, a questionnaire wasapplied to collect data such as professional and personal habits. In order to enhance the research, we used the OWAS method(Ovako Working Posture Analysing System), for a more detailed postural analysis. The study showed that there is a concern withthe professionals regarding their long-term health, since the days of excessive work are constant, associated with no physicalexercise and labor gymnastics. It is concluded that the workstations of this activity are extremely uncomfortable, with numerousnon-compliances as to postures. Therefore, one should conduct a study and propose an alignment or review of furniture andequipment used by dental professionals